PENGARUH PEMBERIAN VIRGIN COCONUT OIL TERHADAP KELEMBABAN KULIT KAKI PADA PASIEN RAWAT JALAN DIABETES MELITUS - Jayanthi, Ketut Dewi (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Foot skin moisture among patients with diabetes mellitus usually decreased. This is due to autonomic neuropathy sudomotorik complications causes a decrease function of sweat and oil glands. Therefore, feet losing its natural ability to moisturize, it become dry and susceptible for infection. Virgin coconut oil is pure coconut oil was made without or with minimal heat processing. Such as body oils, virgin coconut oil serves as a moisturizer binds to sweat by holding water in the stratum corneum. The aim of this study was to determine the effect of virgin coconut oil for foot skin moisture among diabetes mellitus outpatients in Wangaya hospital. This research was a quasy-experimental study (pre-test and post-test with control group design). Samples consisted of 20 patients diabetes mellitus that selected by incidental sampling, which is divided into control and experimental groups. The experimental group was given virgin coconut oil on the respondent’s feet twice a day for 28 days. Foot skin moisture pre-test and post-test in both groups was measured by the skin moisture analyzer. The results show an increase of 15.19% at an foot skin moisture in experimental group, and decrease of 0.39% foot skin moisture in control group. Based on the independent sample t-test, this difference was statistically significant, with value of Sig. (2-tailed) of 0.000, which means there is significant effect of virgin coconut oil for the foot skin moisture among diabetes mellitus outpatients in Wangaya hospital. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: diabetes mellitus; virgin coconut oil; foot skin moisture